Examining the Influence of Maternal Education, Nutritional Knowledge, and Toddler Food Intake on Nutritional Status - Muhasriady Muhasriady; Shyam Sundar Tiwari (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study was to determine the relationship between the level of maternal education, the level of maternal nutritional knowledge and the food intake of toddlers on the nutritional status of toddlers. Methodology: This type of research is an analytical survey with a cross-sectional design. The sample in this study was 54 toddlers obtained using random sampling techniques. The instruments used were questionnaires, 24-hour recall forms, foot scales and height measuring tapes or microtoises. The data obtained in this study were processed using chi-square test statistics. Main Findings: There is a relationship between the level of maternal education and the nutritional status of toddlers with a P value = 0.203 based on BB/A and a P value = 0.847 based on the TB/A index, the level of maternal nutritional knowledge on the nutritional status of toddlers with a P value = 0.990 based on the BB/A index and a P value = 0.171 based on the TB/A index. There is no relationship between food intake and the nutritional status of toddlers in Tamangapa Village, Manggala District, Makassar City with a P value = 0.004 based on energy intake with nutritional status BB/A and a P value = 0.006 TB/A. Novelty/Originality of this study: As a reference material for health workers and the government so that they can provide information and direction to the community, especially mothers, to pay attention to food intake and the development of the nutritional status of their toddlers.